THE INFLUENCE OF INTELLECTUAL CAPITAL AND CORPORATE SOCIAL RESPONSIBILITY ON FIRM VALUE WITH CORPORATE REPUTATION AS AN INTERVENING VARIABLE - Wahyuni, Sri; Yuliusman, Yuliusman; Rahayu, Rahayu (Universitas Nusa Cendana, 2025)
The study aims to determine the effect of intellectual capital and corporate social responsibility on firm value with corporate reputation as an intervening variable in financial companies from various sectors listed on the Indonesia Stock Exchange between 2021-2023. The data analysis approach employs either component-based or variance-based Structural Equation Modeling analysis, commonly referred to as Partial Least Squares (PLS), using SmartPLS software. The results of this study show that intellectual capital has a positive impact on business value and that corporate social responsibility also has a positive impact on business value. However, intellectual capital has no influence on corporate reputation, while CSR has a positive influence on corporate reputation. In addition, corporate reputation also has a positive influence on corporate value. Corporate reputation does not mediate the relationship between intellectual capital and corporate value, but it does mediate the relationship between corporate social responsibility and corporate value. Keywords: Intellectual Capital; Corporate Social Responsibility; Corporate Reputation; Firm Value